Magnetite deformation mechanism maps for better prediction of strain partitioning. Issue 4 (27th February 2013) - Till, J. L.; Moskowitz, Bruce
Abstract: [1] A meta‐analysis of existing experimental deformation data for magnetite and other spinel‐structured ferrites reveals that previously published flow laws are inadequate to describe the general deformation behavior of magnetite. Using updated rate equations for oxygen diffusion in magnetite, we present new flow laws that closely predict creep rates similar to those found in deformation experiments and that can be used to predict strain partitioning between cubic Fe oxides and other phases in the Earth's crust. New deformation mechanism maps for magnetite have been constructed as functions of temperature and grain size. Using the revised creep parameters, estimates of strain partitioning between magnetite, ilmenite, and plagioclase indicate that concentrated zones of Fe‐Ti oxides in oceanic crust near slow‐spreading ridges could accommodate significant amounts of strain at moderate temperatures and may contribute to aseismic creep along spreading‐segment faults. Key Points: New magnetite flow laws can help predict strain partitioning relationships Magnetite is predicted to be capable of significant low‐temperature ductility FeTi‐oxides may contribute to strain localization at slow‐spreading ridges